The technosphere as a new aesthetic - Paić, Žarko 1958-; De Carolis, Massimo 1954-; Fabris, Adriano 1958-; Mersch, Dieter 1951-; Rose, David 1973-; Sorgner, Stefan Lorenz 1973-; Šuvaković, Miško 1954-; Valentić, Tonči; Vita-More, Natasha 1950- (Cambridge Scholars Publishing, 2022)
This edited collection, dedicated to the issue of Homo Kybernetes, sheds light on the genesis and development of opinions about the technosphere as an aesthetic problem par excellence from different points of view. In this sense, the contributions here reflect not only on the cybernetic way of thinking as a condition of the possibility of digital aesthetics, but also on the possibilities of the transition of human sensibility to a different way of bodily existence, starting from transhumanism and the posthuman condition. Zarko Paic is a Professor at the University of Zagreb, Croatia, where he teaches courses in Aesthetics and Media Theory. He publishes frequently in the fields of philosophy, social sciences, and art theory. He is the author of White Holes and the Visualization of the Body (2019) and Neoliberalism, Oligarchy and the Politics of the Event: At the Edge of Chaos (2020), and the editor of Theorizing Images (with Kresimir Purgar, 2016)
Keywords: Ästhetik; Kybernetik; Cybernetics / Philosophy; Computers and civilization; Aufsatzsammlung